Part VII – July 1968 - Papers - 1968 Institute of Metals Lecture - Resistance To Hot Deformation - D. McLean (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
For many pu@oses uniform strength is desired over a long temperature range, coupled to a band of softness at the hot end for easy shaping. Various types of material fulfill such a requirement to different degrees, depending on the regularity of their atomic structure. In long-chain polymers and vitreous glasses the irregular structure leads to a steep temperature dependence of deformation resistance and the temperature band between the hard and brittle condition and the soft condition is only about 100 C. In crystals and especially metals the atomically regular structure leads to a much smaller sensitivity over a wide temperature band, thus approaching the ideal behavim. The reason for this insensitivity is that the regular crystalline structure deforms by the movement of dislocations and the elastic interactions of dislocations in- PLASTICS, GLASSES, AND CRYSTALS The ease or otherwise of deformation varies with temperature much more in some substances than in others. This is an important matter when service over a wide temperature range is needed, especially volve energies of several hundred electron volts compared with which the energy of thermal agitation is insignificant. However, temperature affects a metal's defmmation resistance through its influence on the annealing, m coarsening, of the three-dimensional dislocation network. This coarsening is a phenomenon very similar to grain growth and ideas about grain growth can be applied to it. Taking into account also the temperature dependence of the glide resistance from alloying additions, a reasonable account can be given of the overall effect of temperature on deformation strength and of stress and grain size on deformation rake. Special structures me described. some arising from these ideas and as yet untried, which may benefit metals and polymers but not ni-treous glasses. when in addition a degree of softness suitable for shaping is required at some stage. It would be nice if one could write on this subject in as much detail about plastics, glasses, and so forth, as about metals, but there has been far more study of this matter in metals than in other substances, which is one reason why most of this paper concerns metals. However, in Fig. 1 there are shown the deformation strengths of several nonmetallic substances as a function of temperature. In many tests the attempt at deformation caused breakage and the graph lines are then drawn dashed. Long-chain plastics, a glass, and a crystalline substance are included in Fig. 1. The notable feature of all of them is the sensitivity of the